Pengaruh Kualitas Pelayanan terhadap Keputusan Pasien Memilih Rumah Sakit dengan Dimediasi oleh Kepuasan dan Kepercayaan: Studi Kasus pada Pasien Rawat Inap RSUD Arjawinangun Kabupaten Cirebon - Ocki Bangun Wiranata; Aang Churatman; Dedi M. Siddiq (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
As a Type B teaching hospital, RSUD Arjawinangun is required to deliver comprehensive and high-quality healthcare services. Poor service quality may reduce patient trust and satisfaction, which in turn directly affects the public’s willingness to choose the hospital as an inpatient healthcare provider. This study aims to analyze the effect of service quality on patients’ hospital choice decisions at RSUD Arjawinangun, Cirebon Regency, and to examine the mediating roles of patient satisfaction and patient trust in this relationship. This research employed a quantitative approach with a case study design. The study population consisted of inpatient patients at RSUD Arjawinangun in 2025. Probability sampling was used to determine the sample. Data were collected through questionnaires, and data analysis was conducted using Structural Equation Modeling (SEM) to test both direct and indirect effects among variables. The PLS-SEM results indicate that service quality has a positive and significant effect on patient satisfaction (β = 0.851), patient trust (β = 0.872), and hospital choice (β = 0.853). Patient trust was found to have a significant effect on hospital choice (β = 0.332), while patient satisfaction did not show a significant effect (p = 0.183). Mediation analysis revealed that service quality significantly influences hospital choice through patient trust, but not through patient satisfaction. These findings highlight that trust is a crucial mediator for patient retention in 2025. Patients’ decisions to choose inpatient services at RSUD Arjawinangun are highly dependent on perceived service quality, which is strengthened by the levels of trust and satisfaction formed. Higher service quality—particularly in terms of staff friendliness and physicians’ competence—leads to stronger patient trust and a greater likelihood of returning to the hospital. Recommendation: RSUD Arjawinangun is advised to continuously improve service quality, particularly in the dimensions of responsiveness and tangibles, through facility modernization. Hospital management should integrate patient loyalty programs that focus on building long-term trust through transparent medical information and the optimization of nursing and administrative services to ensure sustained patient satisfaction.